ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA TIKONG, KECAMATAN TALIABU UTARA, KABUPATEN KEPULAUAN SULA - Rosneni La Jauda; O. Esry H. Laoh; Jenny ., Baroleh; Jean F. J. Timban (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine the amount of income from farming cocoa farmers in the village of Tikong, Sub-district of North Taliabu, Sula Islands District. Data analysis method used is the analysis of cost, revenue and income. The results showed that the income of cocoa farmers which have land area of 0.5 to 1,5 Ha is Rp 2,392,749 and income of cocoa farmers who have land area of > 1.5 to 2 hectares is Rp 2,766,69 . In an effort to increase the income of the farming activities of cocoa, farmers in the village of Tikong were trying to increase the production and the size of the land. in order to increase their income.